Mobile eye tracking: new avenues for the study of gaze in social interaction - Zima, Elisabeth; Stukenbrock, Anja (Pragmatics & beyond / New series, 2025)
"This volume explores the crucial role of gaze in human interaction, with a particular focus on the potential of mobile eye tracking to advance our methodology and understanding of multimodal communication. Readers will find a comprehensive, balanced exploration of the benefits and challenges associated with taking eye tracking out of the lab to record authentic interaction in real-life settings. The chapters are written by leading scholars in the field as well as younger researchers. They offer in-depth methodological discussions alongside detailed case studies from static and mobile interaction settings. The book makes a strong case for the use of mobile eye tracking in addition to video cameras. It provides researchers with a solid and state-of-the-art foundation on which to make informed choices about recording technologies for their own work. The volume is a must-read for scholars in multimodal conversation analysis, interactional linguistics, as well as cognitive linguists, linguistic anthropologists, and psychologists with a strong interest in new ways of studying gaze in social interaction"-- Provided by publisher
Keywords: Interaktion; Blick; Augenfolgebewegung; Augenbewegung